Discussion of Toward Experimental Criteria for Judging Disclosure Improvement - Kleinman, David (Journal of Accounting Research, 1969)
David Kleinman, Discussion of Toward Experimental Criteria for Judging Disclosure Improvement, Journal of Accounting Research, Vol. 7, Empirical Research in Accounting: Selected Studies 1969 (1969), pp. 51-54